EFEKTIVITAS EKSTRAK ETANOL TAUGE (VIGNA RADIATA) DALAM MENINGKATKAN KADAR GLUTATION PEROKSIDASE PADA TIKUS PUTIH (RATTUS NORVEGICUS) YANG DIINDUKSI TOLUENA - SUKANTY, NI MADE WIASTY; SAPUTRA, I PUTU BAYU AGUS (Universitas Mahasaraswati K. Mataram, 2023)
Toluene is an industrial volatile compound that is easily inhalable. Excessive exposure to toluene causes health problems because it can increase ROS and cause oxidative stress. Bean sprouts are a plant rich in antioxidants to ward off ROS. The known effectiveness of bean sprout ethanol in increasing antioxidants is uncertain. This study aims to determine the potency of ethanol extract from bean sprouts in increasing the GPX antioxidant levels of white rats induced by toluene. The sample consisted of 30 mice divided into groups K-, K+, P1, P2, and P3. Ethanol extract of bean sprouts is given orally at a dose of 50 mg/200 g BW (P1), 100 mg/200 g BW (P2), and 200 mg/200 g BW (P3) in samples that have been induced before by 0.2 mL toluene/200 g BB for 30 days. MDA and GPX levels were measured using ELISA and tested statistically using the One Way Anova test with α = 0.05. The test results showed that there were no significant differences in MDA levels in all groups (p > 0.05), and there were outstanding differences in GPX levels between the K+ and K- groups (p = 0.001) and P2 (p = 0.009). Based on these results, administering ethanol extract of bean sprouts at 100 mg/200 g BW can increase GPX levels in rats induced by toluene.